Manusia Sebagai Makhluk Eksentris Berdasarkan Profil Pelajar Pancasila - Tuerah, Firmanians Romula; Kukus, Merline Mesti (Peneliti.net, 2023)
Various national problems in various fields of life have created a humanitarian crisis. Even though this nation has a noble vision in building a good civilization as contained in Pancasila. So, an understanding of humanity is needed that is based on Pancasila. Understanding of good humanity can be traced through the Pancasila student profile as an implementation of the Independent Curriculum policy. So the aim of this research is to explore the profile of Pancasila students from the perspective of human philosophy. In this context, this research uses qualitative methods with a literature approach. The results of this research show that the human essence contained in the Pancasila profile is the human relationship with self, others, God and the world. Therefore, humans are understood as eccentric creatures where the center of themselves is outside themselves in relationships. The first and foremost relationship between humans is their relationship with God which guarantees good relationships with God, others, the world and themselves.